Penggunaan Alat Peraga Abakus dalam Meningkatkan Prestasi Belajar Matematika Siswa pada Materi Pokok Operasi Hitung Bilangan Bulat - Abidin, Zainal (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
Based on the results of observations made, it was found that student achievement in learning mathematics was still lacking. This is caused by the lack of teacher creativity in delivering learning materials. For this reason, the author uses abacus teaching aids in improving students' Mathematics learning achievement. The type of research used in this research is Classroom Action Research (CAR). The results showed that there was an increase in the student's average score of 72.91% with learning completeness of 79.16% in the first cycle, and the student's average score of 80% and learning completeness of 87.50% in the second cycle. Based on the results of this study, it can be concluded that the use of abacus teaching aids can improve students' learning achievement in Mathematics.